The intersections of culturally sustaining pedagogies and systemic functional linguistics: affordances for the education of multilingual learners. (22nd February 2021) - de Oliveira, Luciana C.
Abstract: The articles in this issue of Language and Education highlight three important areas of research that have evolved in the education of multilingual learners: (1) culturally sustaining pedagogies (CSP), (2) systemic functional linguistics (SFL) approaches to support learning in elementary and secondary classrooms, and (3) the intersections of CSP and SFL to the development of culturally sustaining systemic functional linguistics pedagogies. This discussion focuses on how these three areas have developed over time and the contributions offered by the articles in this special issue.